The case for offering all women amniocentesis and chromosomal microarray analysis - Beaudet, Arthur (Henry Stewart Talks, 2009)
Array-based copy number analysis (ABCNA), Chromosomal microarray analysis (CMA), CMA methodology, Targeted patient population, Detection of clinically significant abnormalities, Copy number variation, CMA vs. karyotype, Prenatal use of arrays, Microarray genetic screening, Search and destroy concern and eugenics, Tests which should be abandoned, Prenatal CMA clinical protocol, Array-CGH, Findings of uncertain significance, Recent cases, Interpreting uncertain array data, Advantages of amino and array analysis, Two kinds of uncertainty, Non-paternity concerns, Study design
Archived at 2021/02/25